The Study of Collapsible Soil Mixed with Marble Dust: In Case of Adama - Awash Road Project - Mihiret, Rebo (ASTU, 2023)
Collapsible soils present major obstacles in construction and infrastructure projects due to their tendency to shrink when wet, resulting in structural instability and settlement problems. This research investigates the use of marble-based treatment to combat collapsible soils, a common problem in construction and infrastructure development. By varying the percentage of marble content in the soil (ranging from 0% to 50%), the study examines its impact on critical soil properties and collapsibility. The results show that increasing marble content improves soil compaction, reduces water requirements for compaction, and decreases soil plasticity. The maximum dry density steadily rises, indicating improved soil compaction. Simultaneously, the optimum moisture content decreases, reducing the amount of water needed for compaction. Additionally, the liquid limit, plastic limit, and plastic index values all show a favorable trend, indicating a reduction in soil plasticity. Furthermore, the California Bearing Ratio (CBR) values exhibit significant improvement with higher marble content, signifying an increase in the soil's load-bearing capacity. The swelling index decreases, reflecting reduced soil expansiveness as the marble content increases. However, it's worth noting that cohesion values decrease with higher marble content, while the angle of internal friction increases, indicating changes in the soil's shear behavior. The Collapsible Index, which measures how likely the soil is to collapse after being wet, significantly decreases with marble concentration, with numerical values falling from 9.08 at 0% to 1.2 at 50%. CBR values also rise from 22 to 31.5 at the same time. Further demonstrating improved soil shear behavior are direct shear measurements that show better cohesiveness and angle of internal friction values with higher marble concentration. These results highlight the marble-based treatment's potential to considerably reduce soil collapsibility. The Collapsible Index and CBR values' numerical representations vividly show the significant advancements made, highlighting the research's application to soil stabilization and infrastructure construction. With the potential for widespread application in areas afflicted by collapsible soils, this study offers insightful information for geotechnical engineering practices. It is advised to conduct more studies and field testing to examine the long-term performance and environmental effects of marble-based soil treatment.
Keywords: Soil Stabilization; Waste Marble Dust; Collapsible Soils